1976. Using a Patient Portal as a Recruitment Tool to Diversify the Pool of Participants in COVID-19 Vaccine Clinical Trials. (15th December 2022) - Yuh, Tiffany; Srivastava, Tuhina; Fiore, Danielle; Schmidt, Harald; Frank, Ian; Metzger, David; Momplaisir, Florence
Abstract: Background: Because the COVID-19 pandemic disproportionately affected racial/ethnic minorities in the US, there was a push to ensure diversity in COVID-19 vaccine clinical trials. Historically, minority groups have been underrepresented in research. We assessed the feasibility of recruiting racial/ethnic minorities through an electronic health record (EHR) patient portal. Methods: The UPenn Health System EHR was used to identify individuals ages 40 and older, living in zip codes with high rates of SARS-CoV-2 test positivity, with a risk factor associated with severe COVID-19 disease. Eligible individuals with an activated patient portal account were sent a message inviting them to participate in the COVID-19 vaccine clinical trial. A follow-up phone call was made to those who did not respond or declined, and reasons for or against participation were coded to extract themes. Results: In August 2020, a total of 13, 779 patients fit the inclusion criteria, of which 5, 614 (40.7%) had an activated patient portal account and were invited to participate. The majority, 5, 426 (96.7%), identified as black, and 73 (1.3%) identified as Hispanic/Latinx. Only 301 (5.4%) of messaged individuals responded. Among respondents, 55 of 206 (26.7%) blacks, 5 of 7 (71.4%) Hispanic/Latinx, and 50 of 76 (65.8%) whites expressed interest. Among the 115 respondents who expressed interest, 24 agreed to a screening visit, and 9 were ultimately enrolled in the trial, which consisted of 6 black, 3 white, and 1 Hispanic/Latinx individual. During phone outreach to those who did not respond and those who declined, common reasons for declining included underlying health conditions, fears of an unproven vaccine, not wanting to be experimented upon, the rapid speed of vaccine development, and the lack of time to participate in a trial. Patient portal response rates by race/ethnicity Conclusion: Because of low rates of patient portal account activation and use, compounded with vaccine hesitancy, recruitment of racial/ethnic minorities into COVID-19 vaccine clinical trials through patient portal messaging yielded a small number of participants. Strategies to increase use of the patient portal combined with approaches to address concerns of trial participation should be considered to increase enrollment of racially/ethnically diverse groups into vaccine clinical trials. Disclosures: All Authors : No reported disclosures.